Penerapan Model Pembelajaran Problem Based Learning (PBL) untuk Meningkatkan Hasil Belajar Peserta Didik Kelas XI MIPA 3 SMAN 2 Mataram - Hapsari, Rawindy Aulia; Rahmawati, Nining; Setiadi, Dadi (Program Studi Magister Pendidikan IPA, Universitas Mataram, 2023)
Problem Based Learning (PBL) model is a problem-based learning model that involves students to solve a problem so that students gain knowledge and have skills in solving problems. This is an effort to improve 21st century skills. This collaborative classroom action research aims to improve the learning outcomes of class Data collection techniques through observation, interviews, and written tests (cognitive). This research was conducted in two cycles, each cycle consisting of planning, action, observation and reflection. Data analysis uses qualitative descriptive analysis. The research results show that the application of the Problem Based Learning learning model can improve the learning outcomes of class XI MIPA 3 students at SMAN 2 Mataram for the 2022/2023 academic year. This can be seen from the average value of learning outcomes in cycle I of 78 with classical completeness of 72.2% (high category) and in cycle II there was an increase with average learning outcomes of 82 with classical completeness of 80.5% ( high category).